Dynamic bifurcation analysis and mitigation of SSR in SMIB system - Shruthi Ramachandra; Mala R.C.; H. V. Gururaja Rao (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a detailed study on Sub-synchronous resonance in a Single machine connected to an infinite bus system by employing Bifurcation Theory. The synchronous machine model considered is a two-axis model, the turbine system is a six mass system. A comparative study of Sub-synchronous resonance for the two-axis synchronous machine models 1.1, 2.1 and 2.2 under constant excitation is presented in this paper. The effect of adding an exciter, power system stabilizer and Static Synchronous Series Compensator to the SMIB system, incorporated with a 2.2 synchronous machine model on the bifurcations of SSR is also investigated. The results obtained on replacing the fixed series compensation of the line by Static Synchronous Series Compensator resulted in the mitigation of Sub-synchronous Resonance. The results obtained for all the above-considered cases are compared with eigenvalue analysis and validated using transient analysis.